Thirty day prognosis of patients with acute pulmonary oedema complicating acute coronary syndromes. Issue 7 (14th June 2005) - Figueras, J; Peña, C; Soler-Soler, J
Abstract : Objectives: To investigate the characteristics of the acute coronary syndromes underlying acute pulmonary oedema and their 30 day prognosis. Patients: 185 consecutive patients with acute coronary syndromes and acute pulmonary oedema admitted to a tertiary care centre. Main outcome and measures: Clinical, ECG, echocardiographic, enzymatic, and angiographic features were prospectively investigated. Results: Non-ST segment elevation myocardial infarction (NSTEMI) was the most frequent cause of acute pulmonary oedema (61%) followed by unstable angina (UA; 21%) and ST segment elevation myocardial infarction (STEMI; 18%). In each group, mean age was ⩾ 70 years, but NSTEMI patients were the oldest and ⩾ 65% of patients had chronic hypertension. Moreover, patients with NSTEMI and UA were older and had a higher incidence of diabetes, previous myocardial infarction, and moderate to severe mitral regurgitation but a similarly reduced ejection fraction (NSTEMI, 41%; UA, 39%; and STEMI, 39%) and increased incidence of diastolic dysfunction and rate of multivessel disease (94%, 87%, and 86%, respectively). However, patients with STEMI had a higher creatine kinase MB peak concentration (158 v 76 μg/l in the NSTEMI group, p < 0.001) and 30 day mortality (26% v 9% in the NSTEMI group and 8% in the UA group, p < 0.024). Multivariate analysis identified ejection fraction < 40% and a peak creatine kinase MB concentration > 100 μg/l as the main prognostic markers (p < 0.03). Conclusions: Acute pulmonary oedema is mostly a complication of elderly hypertensive patients with NSTEMI or UA (82%) and with multivessel disease often associated with mitral regurgitation. On the other hand, the larger infarct size and higher mortality in patients with STEMI with a similarly reduced ejection fraction suggest a more extensive acute systolic loss.